54 Incidence of sport-related internal organ injuries due to direct contact mechanisms among high school and collegiate athletic participants across three national surveillance systems. (19th September 2017) - Kucera, Kristen; Currie, Dustin; Wasserman, Erin; Kerr, Zachary Y; Thomas, Leah; Paul, Stephen; Comstock, Dawn
Abstract : Purpose: Describe the incidence and characteristics of sport-related internal organ injuries due to direct contact mechanisms among high school (HS) and collegiate athletic participants from 2005/06–2014/15. Methods: Data from three national sports injury surveillance systems were analysed: High School Reporting Information Online (RIO; HS), National Collegiate Athletic Association Injury Surveillance Program (ISP; college), and the National Centre for Catastrophic Sport Injury Research (NCCSIR; college and HS). Internal organ injuries were defined as: affecting the internal organs (e.g., kidney, lung); due to direct contact mechanism; resulting in medical care and time loss of 1 or more days (RIO and ISP) or temporary or permanent disability or death (NCCSIR). Descriptive statistics (stratified by surveillance system) included frequencies and incidence rates per 1, 000, 000 athlete-exposures and 95% confidence intervals (IR: 95% CI). Results: During the ten-year period, 174 internal organ injuries were captured across the three systems: 124 HS (RIO); 41 collegiate (ISP); and 9 catastrophic (NCCSIR). Most non-catastrophic internal organ injuries occurred among males (85% RIO; 89% ISP), in football (65% RIO; 58% ISP), during competition (67% RIO; 49% ISP) and due to player-player contact (78% RIO; 68% ISP). The highest rates of injury were in male contact sports: RIO: HS football (IR=11.7: 9.1–14.2), HS lacrosse (IR=10.0: 3.1–16.9); ISP: college football (IR=8.3: 5.0–11.6), college ice hockey (IR=7.9: 1.0–14.7). A quarter of internal organ injuries were season-ending (25% RIO; 23% ISP). Of the 9 catastrophic injuries (NCCSIR), most occurred in high school (7/9) and football (7/9) and were due to player-player contact (6/9). Four resulted in death and 5 resulted in disability. Conclusions: Direct contact internal organ injuries occur infrequently, yet when they do occur, may result in severe outcomes. Significance: These findings suggest early recognition and a better understanding of the activities associated with the event and use/non-use of protective equipment is needed.